Experimental study using ASTM and BS standards and model evaluations to predict the compressive strength of the cement grouted sands modified with polymer - Wael Emad; Ahmed Salih; Rawaz Kurda (Case Studies in Construction Materials, 2021)
The present article discusses the impact of the different grain sizes of sand on the ultimate stress of hand-mixed cement grouted sand modified with polycarboxylate ether-based polymer using two different test standards (ASTM and BS). The fresh and hardened properties of cement grouted sands modified with polymer up to 0.16 % of the weight of cement were tested and quantified. Five types of sand with different grain sizes were used in this study. Adding polymer decreased the water/cement ratio (w/c) by 21.9–54.1%, and it kept the flow time of the cement-based grout in the range of 18–23 s. Adding polymer creates an amorphous gel that fills the porous between the cement particles, which causes a reduction in the voids, porosity and enhanced the dry density of the cement; subsequently, the compression strength of the cement-grouted sands increased significantly. Linear and nonlinear approaches were employed to estimate the compressive strength of cement grouted sand with a different grain size of sand, w/c, amount of polymer, and curing age. The compressive strength of the cement grouted sands following the BS standard was 71 % larger than the compression strength of the same mix using the ASTM standard.